Quality Assessment of Dry Fishes of Bangladesh with the Special Emphasis on Harmful Additives - Bhuiyan, M Nurul Huda; Dawlatana, Mamtaz; Bhuiyan, Habibur Rahman; Lucky, Farhana Akter; Saha, Barun Kanti; Bhuiyan, M Nazrul Islam (Bangladesh Journal of Scientific and Industrial Research, 2010)
Proximate biochemical analysis and screening of organochlorine insecticides (Heptachlor and DDT) of six dry fish samples namely Bombay duck (Loittya), Ribbon fish (Chhuri), Anchovy (Teilla phasa), Croaker (Poa), Chinese pomfret (Rupchanda) and Indian salmon (Lakhua) were analyzed to assess the quality of dry fishes of Bangladesh. The fish samples were concentrated source of protein (minimum 42.50% in Indian salmon to maximum 64.51% in Ribbon fish) and ash (mineral) (minimum 0.21% in Indian salmon to maximum 6.44% in Croaker fish). Organochlorine insecticides (DDT and Heptachlor) were found in all the samples of dry fish analyzed. The minimum concentration of Heptachlor and DDT were found in Ribbon fish (0.778 ppb) and in Chinese pomfret (7.849 ppb) respectively and the maximum concentration of Heptachlor and DDT were found in Chinese pomfret (54.753 ppb) and in Indian salmon 233.727 ppb respectively. Key words: Dry fish, Concentration, Organochlorine insecticides, DDT, Heptachlor, Proximate analysis. DOI: 10.3329/bjsir.v44i3.4404 Bangladesh J. Sci. Ind. Res. 44(3), 311-318, 2009